An Archaeology of the Interior Case Studies: The Archaeology of Obsolete Stairs - Istiani, Noor Fajrina Farah (Bina Nusantara University, 2022)
This paper discusses the possibility of adopting the study of archaeology as known in cultural theory to redesign the obsolete interior architecture element. The archaeological discipline might offer a possibility to understand the interior element thoroughly through emphasizing the specific material characteristics and their correlation to the different periodical lifetimes of the context. The idea of the archaeology of an interior introduces well-recorded analysis and material experimentation in the physical translation of interior elements. The design process is mainly conducted by emphasizing the notion of